NEONATAL COMPLICATIONS IN NEWBORNS OF ADOLESCENT MOTHERS AT DANIELALCIDES CARRIÓN NATIONAL HOSPITAL IN CALLAO, 2021 - Díaz Guerrero, Diana Carolina (2024)
Introduction. Adolescent pregnancy is a global issue associated with neonatal complications. Objective. To determine the neonatal complications associated with adolescent mothers attended at the Daniel Alcides Carrión National Hospital in 2021. Materials and Methods. An observational, analytical, cross-sectional, and retrospective study was conducted. The dependent variable was the presence of neonatal complications, while the independent variables included maternal age and other demographic factors. The sample consisted of 320 newborns, and a statistical power of 97.53% was calculated using OpenEpi. Results. Of the 320 newborns, 78.8% were born to mothers aged 17-19 years, and 21.2% to mothers aged 10-16 years. 22.5% had complications, the most frequent being prematurity (20.9%), jaundice (20.3%), small for gestational age (8.4%), and respiratory distress (6.9%). A significant association was found between an inadequate number of prenatal visits (0-5) and neonatal complications (adjusted PR: 3.32; 95% CI: 2.27-4.84; p < 0.001), while maternal age did not show a significant association in the adjusted analysis (adjusted PR: 1.30; 95% CI: 0.84-2.02; p = 0.232). Conclusion. An inadequate number of prenatal visits is associated with a higher risk of neonatal complications in newborns of adolescent mothers.